2021
DOI: 10.3390/educsci11100628
|View full text |Cite
|
Sign up to set email alerts
|

Using Machine Learning Approaches to Explore Non-Cognitive Variables Influencing Reading Proficiency in English among Filipino Learners

Abstract: Filipino students ranked last in reading proficiency among all countries/territories in the PISA 2018, with only 19% meeting the minimum (Level 2) standard. It is imperative to understand the range of factors that contribute to low reading proficiency, specifically variables that can be the target of interventions to help students with poor reading proficiency. We used machine learning approaches, specifically binary classification methods, to identify the variables that best predict low (Level 1b and lower) v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 69 publications
2
5
0
Order By: Relevance
“…One factor that may be increasingly important in identifying poor science achievers is access to ICT devices with internet access. Studies on Filipino students; PISA achievement in reading (Bernardo et al, 2021 ) and mathematics (Bernardo et al, 2022 ) also found the same factor as a predictor of achievement, consistent with much of the research in other countries (Hu et al, 2018 ; Petko et al, 2017 ; Yoon and Yun, 2023 ; but see Bulut and Cutumisu, 2018 ). Presumably, access to the internet outside the school environment has become an important resource for learning science; perhaps not just for accessing relevant scientific knowledge available online but also as a means of communicating with classmates for information sharing, collaboration in learning activities, and supporting each other’s motivations and engagement in science learning.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…One factor that may be increasingly important in identifying poor science achievers is access to ICT devices with internet access. Studies on Filipino students; PISA achievement in reading (Bernardo et al, 2021 ) and mathematics (Bernardo et al, 2022 ) also found the same factor as a predictor of achievement, consistent with much of the research in other countries (Hu et al, 2018 ; Petko et al, 2017 ; Yoon and Yun, 2023 ; but see Bulut and Cutumisu, 2018 ). Presumably, access to the internet outside the school environment has become an important resource for learning science; perhaps not just for accessing relevant scientific knowledge available online but also as a means of communicating with classmates for information sharing, collaboration in learning activities, and supporting each other’s motivations and engagement in science learning.…”
Section: Discussionsupporting
confidence: 62%
“…There is a lot of evidence that good reading strategies and reading comprehension are strongly associated with science achievement (Cano et al, 2014 ; Caponera et al, 2016 ; Kolić-Vrhovec et al, 2011 ), but Filipino learners on average have extremely poor reading skills in English (Bernardo et al, 2021 ), which is the medium-of-instruction in science. Presumably, there are science learning activities that are more experiential and discovery-oriented and less dependent on students’ reading textbooks; but a previous study of students’ perception of science classes revealed a trend of decreasing science inquiry activities accompanied by an increase in self-learning, presumably involving reading textbooks and learning modules from Grade 5 to 10 (Bernardo et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Survey-driven measures, such as those in most studies presented in this work, have been widely used in AA research. Recent research [55] has suggested that data-driven research using machine learning techniques could complement the more traditional research approach and produce more accurate results, capitalizing on the massive amount of information available to educational institutions [56]. For example, Cruz-Jesus et al [57] employed artificial intelligence techniques to assess AA drivers in high school, using a database from all public high schools in Portugal.…”
Section: Discussionmentioning
confidence: 99%